Nutritional Status and Knowledge of Mothers Regarding the Incidence of Anemia in Pregnant Women (Systematic Review) - Karlina, Lini; Cicih, Lilis Heri Mis (Jurnal Kesehatan Masyarakat Perkotaan, 2025)
Anemia can be defined as a condition in which the body does not have sufficient red blood cells, even though erythrocytes contain hemoglobin, which is responsible for carrying oxygen throughout the body. Anemia in pregnant women is a significant public health problem in Indonesia. Based on the 2018 Basic Health Research (Riskesdas), the prevalence of anemia in pregnant women reached 48.9%, indicating a high health burden due to this condition. This study aims to analyze the relationship between nutritional status and maternal knowledge levels with the incidence of anemia in pregnant women. The research method used a systematic review with a literature search in the PubMed and Google Scholar databases for the period 2019-2024 using keywords related to nutritional status, maternal knowledge, and anemia. Of the total 4,520 publications obtained, 13 relevant articles were systematically selected, based on inclusion and exclusion criteria. The review results showed a significant relationship between nutritional status and the incidence of anemia in pregnant women (p<0.05), where mothers with poor nutritional status were at higher risk of developing anemia. In addition, maternal knowledge levels also showed a significant relationship with the incidence of anemia (p<0.05), where insufficient knowledge increased the risk of anemia. This study concludes that maternal nutritional status and knowledge are two important factors that are interrelated in determining the risk of anemia in pregnant women, so efforts are needed to increase nutrition and health education to reduce the prevalence of anemia in pregnant women in Indonesia.